2022
DOI: 10.1007/s10072-022-06426-9
|View full text |Cite
|
Sign up to set email alerts
|

Teleneuropsychology: normative data for the assessment of memory in online settings

Abstract: Introduction The COVID-19 pandemic has forced significant changes in clinical practice. Psychologists and neuropsychologists had to modify their settings to assess patients’ abilities, switching from an in-person modality to a remote setting by using video calling platforms. Consequently, this change brought about the need for new normative data tailored to remote settings. Aim and methods The study aimed to develop normative data for the online assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In remote cognitive evaluation, the need to adapt administration modalities is the main issue in terms of reliability and validity. Furthermore, specific normative data are required to interpret tests’ results in this condition, but few efforts have been made in this direction [34] , [35] , [36] . Current recommendations are to rely on normative data obtained using the standard assessments for those cognitive tests proven to be consistent across conditions, but caution is needed in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…In remote cognitive evaluation, the need to adapt administration modalities is the main issue in terms of reliability and validity. Furthermore, specific normative data are required to interpret tests’ results in this condition, but few efforts have been made in this direction [34] , [35] , [36] . Current recommendations are to rely on normative data obtained using the standard assessments for those cognitive tests proven to be consistent across conditions, but caution is needed in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of the first ethical and practical guidelines (Grosch et al, 2011), TeleNP validity has been successfully demonstrated (Marra et al, 2020) as to both cognitive screeners and domain-specific tests (language, attention, and memory; e.g., Rizzi et al, 2023). However, these studies addressed mainly verbal cognitive tests, which are often administered orally, therefore facilitating their adaptation to remote media (e.g., telephone, video call).…”
Section: Vanit: Three Guiding Principles For Test Selectionmentioning
confidence: 99%
“…Hence, establishing age norms or benchmarks with validated real-time HRVB metrics is crucial for personalizing care (Fernandes et al, 2017;Kessler & Luedtke, 2021). Most prior HRVB studies, however, have employed small sample sizes (20-150 participants), which preclude norms and limit ecological validity (Pizzoli et al, 2021;Rempfer & Fowler, 2018;Rizzi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%